2009
DOI: 10.1001/jama.2009.975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduced-Dose Schedules With 7-Valent Pneumococcal Conjugate Vaccine on Nasopharyngeal Pneumococcal Carriage in Children

Abstract: HE SUCCESS OF THE INTRODUCtion in 2000 in the United States of routine infant vaccination with the licensed 7-valent pneumococcal conjugate vaccine (PCV-7) is based on direct protection against vaccine serotype pneumococcal disease among vaccinees but also on the observed and unexpectedly large and widespread reduction in invasive and respiratory (eg, pneumonia and otitis media) vaccine serotype pneumococcal disease in nonimmunized individuals (indirect effect or herd protection). 1-6 This herd effect has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
154
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(175 citation statements)
references
References 43 publications
18
154
2
1
Order By: Relevance
“…Second, the postvaccination data came from a cross-sectional cohort study including 2 separate age groups, whereas the pre-PCV7 control data were derived from a longitudinal study in which data were collected from the same children at age 12 and 24 months. However, we previously found that potential within-person dependency was not substantially affecting these carriage data, probably because of the large interval between carriage sample collections (13). Third, the study was not adequately powered to evaluate serotype-specifi c differences.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Second, the postvaccination data came from a cross-sectional cohort study including 2 separate age groups, whereas the pre-PCV7 control data were derived from a longitudinal study in which data were collected from the same children at age 12 and 24 months. However, we previously found that potential within-person dependency was not substantially affecting these carriage data, probably because of the large interval between carriage sample collections (13). Third, the study was not adequately powered to evaluate serotype-specifi c differences.…”
Section: Discussionmentioning
confidence: 95%
“…Transoral swabs of the directly observed posterior pharynx were collected on a rigid cotton-wool swab. All swabs in both studies were processed according to the same study procedures by the same laboratory for microbiology as described (13). Briefl y, swabs were cultured for S. pneumoniae, then 1 pneumococcal colony per plate was subcultured and serotyped by the capsular swelling method (Quellung reaction).…”
Section: Nasopharyngeal Swabsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Municipal Council in Kielce decided to apply the 2+1 scheme, as it was not only cheaper, which was a particularly important factor in this case, but also, as evidenced in numerous studies [13,15,16,28], was as efficient in a mass vaccination pattern as the original 3+1 scheme. The scheme was, thus, approved for population vaccination also in the registration dossier.…”
Section: Discussionmentioning
confidence: 99%
“…Children and their parents were tested for NP carriage of S. pneumoniae at 12 months, 18 months and 24 months of age. In the two vaccinated groups, fewer children and their parents were colonized with S. pneumoniae (24) compared to controls suggesting that herd immunity can be maintained with two or three doses of PNEU-C-7. (25) Within the European Union, in 2009, 11 of 24 countries reporting PNEU-C-7 programs used a three-dose schedule for all children, and a twelfth (Switzerland) recommended a three-dose schedule for healthy children but a four-dose schedule for children with chronic conditions increasing their risk of IPD.…”
Section: Recent Literature Regarding Vaccination Schedulesmentioning
confidence: 94%